Közjogi elemek a Kálmán korabeli jogforrásokban - László, Balázs (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The royal regulations protecting the interests of the Christian church and property are usually considered to represent the legal significance of the Kálmán era. However, the contemporary decrees, privileges (letters patent) and other written documents – all of which is a kind of sources of law – also describe some of the basic institutions of the state and public law. We can find regulations and descriptions concerning legislation, administration, judicial power, fiscal policy, church administration, warlordism and diplomatics. Most of these regulations can be related to the royalty, the royal rights and prerogatives representing the fundamental role of the monarch in the state. On the other hand, they also represent the appearance and development of other elements of the operating state.